Deteksi Kerusakan Dalam Bentuk Kebocoran Dan Sumbatan Elbow Pipa Menggunakan Sinyal Suara Dan Delapan Mikrofon - Raynold Harlem Hutasoit; Feblil Huda (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
In this study, damage to the pipe was detected using a voice signal and eight microphones. The voice signal method is a smart structural health monitoring that can detect damage at a lower cost. Sound excitation is givenusing a loudspeaker and the response of the sound signal is sampled using eight microphones connected to a PC-Oscilloscope which functions to convert the analog signal from the recorded sound into a digital signal inthe form of a time domain value and then uses a Continuous Wavelet Transform (CWT) to determine the location of the damage. occurs in the pipe sheath. To detect the location of pipe damage in various damage positions, itcan be searched by comparing the wavelet coefficient and seen on the polar plot of eight microphones. The damage given is in the form of plugs and leaks with different distances and positions. From the experimentalresults obtained for a single pipe with leaking conditions on leaking pipe testing 0.7 m in the direction of 210º it can be seen that the highest wavelet coefficient value occurs at microphone 6 and microphone 5 which is0.01374 and 0.01274 according to the location of the damage that occurred in the an angle of 210º between 180º and 225º. It can be seen the location of the damage position in the pipe casing through the polar plot, the pointthat is further away from the outer circle on the 6-way microphone 225º and the 5-way microphone 180º is the position of the location damage pipe.Keywords : Sound Signal, Leakage, Blockage, Fast Fourier Transform, Wavelet Transform, Polar Plot.